2006
DOI: 10.1111/j.1529-8817.2006.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHETIC PERFORMANCE, LIGHT ABSORPTION, AND PIGMENT COMPOSITION OF MACROCYSTIS PYRIFERA (LAMINARIALES, PHAEOPHYCEAE) BLADES FROM DIFFERENT DEPTHS1

Abstract: Macrocystis pyrifera (L.) C. Agardh is a canopyforming species that occupies the entire water column. The photosynthetic tissue of this alga is exposed to a broad range of environmental factors, particularly related to light quantity and quality. In the present work, photosynthetic performance, light absorption, pigment composition, and thermal dissipation were measured in blades collected from different depths to characterize the photoacclimation and photoprotection responses of M. pyrifera according to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 43 publications
10
86
2
4
Order By: Relevance
“…Experimentally they also showed that M. pyrifera could not withstand temperatures higher than 24 • C, and specimens perished after 5 days. Nevertheless, in northern Baja California M. pyrifera populations are exposed to SST variations of between 12.7 • C to 22.5 • C, while the southernmost subtropical populations show warmer temperature tolerances varying between 15.6 • C to 25.5 • C [103]. It is already well established that climate changes can affect substantially species distribution and, more particularly, alter the rafts' trajectory, which will influence the dispersal and distribution of marine organisms [46,96,104].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally they also showed that M. pyrifera could not withstand temperatures higher than 24 • C, and specimens perished after 5 days. Nevertheless, in northern Baja California M. pyrifera populations are exposed to SST variations of between 12.7 • C to 22.5 • C, while the southernmost subtropical populations show warmer temperature tolerances varying between 15.6 • C to 25.5 • C [103]. It is already well established that climate changes can affect substantially species distribution and, more particularly, alter the rafts' trajectory, which will influence the dispersal and distribution of marine organisms [46,96,104].…”
Section: Discussionmentioning
confidence: 99%
“…Kelp canopy density was quantified as the area (m 2 ) of blade tissue in the surface canopy per m 2 of sea surface. We chose this metric to characterize kelp bed density because the majority of the biomass of Macrocystis pyrifera is contained in the canopy where most nitrate uptake and photosynthesis occur (Towle & Pearse 1973, Wheeler & Srivastava 1984, Colombo-Pallotta et al 2006. The density of canopy fronds in the Mohawk kelp bed was measured monthly in the center of the kelp bed as part of an ongoing monitoring program by the Santa Barbara Coastal Long Term Ecological Research project (SBC-LTER; Rassweiler et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, light availability within a kelp bed may be as much a function of canopy density as it is ambient sunlight. As a result, light in the interior of a kelp bed may be reduced to levels that inhibit nutrient uptake and photosynthesis in M. pyrifera (Gerard 1986, Colombo-Pallotta et al 2006) and understory macrophytes (Stewart & Carpenter 2003). Such effects caused by the kelp canopy are reduced by winter storms that thin or remove the canopy, thereby increasing light and nutrient penetration into the bed, and allowing for recruitment and growth of young kelp that would otherwise be out-competed for light by the surface canopy (Reed & Foster 1984, Dean et al 1989, Watanabe et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…(9) analytically is difficult and numerical integration is recommended. (Wheeler 1980, Gerard 1986, Colombo-Pallotta et al 2006). Our blade-averaged fluxes agreed well with reported values at low u ∞ , but were lower than has been previously reported at high u ∞ .…”
Section: Discussionmentioning
confidence: 99%